Widziane z trzeciego planu - Mlynczak, Tadeusz Witold; Herz, Janusz (Warszawa : Polska Oficyna Wydawnicza "BWG,", 1992)
An interview with a 56 year old leader of one of the new political parties in Poland.
Keywords: Mlynczak, Tadeusz Witold -- Interviews; Stronnistwo Demokratyczne; Politicians -- Poland -- Interviews